Microwave harmonic generation and nonlinearity in microplasmas. (19th April 2016) - Gregório, José; Parsons, Stephen; Hopwood, Jeffrey
Abstract: Nonlinearities in microplasmas excited by microwaves are described both experimentally and through a 2D fluid model. A split-ring resonator generates a microplasma in a 150 μ m discharge gap at 1 GHz. Nonlinearity generates both radiated and conducted harmonics which are measured from 0.2–760 Torr (Ar) for power levels between 0.5 and 3 W. Asymmetric electrode configurations produce the highest 3rd harmonic power (>10 mW) at an optimal pressure of the order of 0.3 Torr. The microplasma is also demonstrated as a mixer. The experimental results are explained with the aid of a fluid model of the microplasma. The model shows that the smaller electrode in an asymmetric device is forced to attain a large microwave potential that strongly modulates the sheath thickness and the local electron energy. The voltage-dependent sheath width gives rises to a nonlinear sheath capacitance as well as short pulses of hot electron flux to the electrode. The modeled 3rd harmonic current is converted to an extractable harmonic power by a microwave circuit model. Using this technique the modeled and measured harmonic production of the microplasma are found to compare favorably.